1992
DOI: 10.1007/bf02047868
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fissure-in-ano

Abstract: A prospective study comparing open and subcutaneous lateral internal sphincterotomy for chronic anal fissure was conducted. One hundred twelve patients were randomized to open (n = 54) or subcutaneous (n = 58) sphincterotomy. There was no significant difference in acute complications between the subcutaneous (8.6 percent) and open (7.4 percent) groups. Postoperative length of stay was significantly shorter for the subcutaneous group (1.7 +/- 0.2 days) than for the open group (2.3 +/- 0.1 days; P less than 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…It remains the surgical treatment of choice for chronic anal fissures that are refractory to medical treatment (166,167). Healing rates have been reported between 94% and 98% (147,148,168) and are clearly superior to uncontrolled manual anal dilation, with better healing rates and less incontinence (167). It is also more efficacious than any topical (169) or injectable treatment (170).…”
Section: Surgical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains the surgical treatment of choice for chronic anal fissures that are refractory to medical treatment (166,167). Healing rates have been reported between 94% and 98% (147,148,168) and are clearly superior to uncontrolled manual anal dilation, with better healing rates and less incontinence (167). It is also more efficacious than any topical (169) or injectable treatment (170).…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…It is also more efficacious than any topical (169) or injectable treatment (170). There is no outcome difference between open and closed sphincterotomy, and thus, a minimal-incision approach is probably preferred (148,168,171). However, there is a low but real incidence of FI from LIS (172), and hence, surgeons continue to explore alternative interventions (173,174).…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Multiple, well-designed comparative studies have demonstrated that there are no significant differences in outcomes between properly performed open and closed surgical sphincterotomies, with healing rates of 90% to 100% and 85% to 100%, respectively, and minor FI rates of 5% to 25% and 2.5% to 25%, respectively. 54,[67][68][69][70] A Cochrane analysis of 5 studies including 336 patients also confirmed this finding, reporting no statistical difference with regard to fissure healing (OR 1.00, 95% CI, 0.40-2.48) and incontinence to flatus (OR 0.87; 95% CI, 0.41-1.83). 54 With regard to postoperative pain and complication rates, a randomized study of 136 patients demonstrated that open sphincterotomy was associated with significantly higher postoperative pain scores and a 4.4% delayed healing rate of the surgical site at 1-year follow-up in the open group, compared to no delayed healing in the closed group (p = 0.08).…”
Section: Lis Is the Treatment Of Choice For Chronic Anal Fissures In ...mentioning
confidence: 78%
“…26,27 LIS has been proven highly effective in curing anal fissures in a number of randomized clinical trials, with success rates higher than 90%. 13,14,[28][29][30][31] It encompasses an overall risk of incontinence, which can be as high as 10%. 15 Hence, the interest in seeking new medical treatments is directed at lowering the tone of the IAS.…”
Section: Discussionmentioning
confidence: 99%